(untitled) (Journal of Universal Science Research, 2024)
The relevance of the study of the topic of this article is due to the growing interest on the part of the scientific community, government agencies, and business circles in the problem of creating, stimulating, and promoting innovations. The development of an innovative environment is a determining factor in the favorable growth of the national economy. In turn, it is venture capital that becomes a tool for supporting and implementing innovations in various industries. At the same time, venture financing is still an unsettled phenomenon in modern science. The problem of the study is to characterize the phenomenon of venture capital as a system that is essential for the search and implementation of new ideas and technologies in the socio-economic life of society, and not as isolated precedents for financing young innovative projects in order to obtain super-profits. The purpose of this study is to clarify the essence of venture capital, the features of financing innovative start-ups and to determine current trends in the development of venture financing. The scientific significance of the study lies in the fact that the author conducted a theoretical analysis of the interpretation of the concept of “venture capital”, presented the subject structure of venture financing, and assessed the role of the state in the development of the innovative investment environment in Uzbekistan.